Safety evaluation on central separation opening of reconstructed freeway based on surrogate safety assessment model. (26th November 2021) - Hou, Wei; Du, Zijun; Liu, Zhaoxin; Wang, Xu
In order to reduce the risk of driving at the opening of the median strip of the old road of the freeway, driving safety was quantified by taking the opening length of the central section of the old road and the main line flow as independent variables. Based on the VISSIM micro-simulation software, a typical simulation scenario is established. The vehicle speed, the position of the vehicle's change point, the number of conflicts, the severity of the conflict, and the conflict points are analysed by the surrogate safety assessment model (SSAM). The influence of the opening length of different median strips and the influence of flow on safety is quantitatively evaluated, so as to obtain a reasonable opening length of the median strip. The research results show that the flow has a greater impact on the number of collisions, and the length of the open section has a significant impact on the severity of the conflict. The conflict points are found to be concentrated at the front of the 400 m open section. The results of the study provide a theoretical basis for the opening length of the median strip and the setting of traffic signs.